2005
DOI: 10.1177/153331750502000511
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation of anti-ß amyloid antibodies inhibits microglia activation in BV-2 cellular model

Abstract: Immunotherapy has become a strategy for treatment of Alzheimer's disease, by inducing antibody response to amyloid-beta peptide (AbetaP) or by passive administration of anti-AbetaP antibodies. Clearance of amyloid plaques involves interaction of immunoglobulin Fc receptor (FcR)-expressing microglia and antibodyopsonized Abeta deposits, stimulating phagocytosis but may promote neuroinflammation. Carbohydrate moiety of Fc of the immunoglobulin G molecule plays a significant role in modulating binding to FcR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Deglycosylated antibodies showed limited ability to activate immortalized microglia, BV-2, in vitro (Rebe & Solomon, 2005). In addition, chronic treatment with deglycosylated antibody against the C terminus of Abeta 40, in comparison with intact antibody, is associated with reduced accumulation of CD45-immunopositive activated microglia surrounding plaques and improved cognitive performance in an AD model mouse in vivo (Carty et al, 2006;Wilcock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Deglycosylated antibodies showed limited ability to activate immortalized microglia, BV-2, in vitro (Rebe & Solomon, 2005). In addition, chronic treatment with deglycosylated antibody against the C terminus of Abeta 40, in comparison with intact antibody, is associated with reduced accumulation of CD45-immunopositive activated microglia surrounding plaques and improved cognitive performance in an AD model mouse in vivo (Carty et al, 2006;Wilcock et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being effective, systemic administration of anti-Aβ antibodies using unmodified IgG can provoke neuroinflammation via microglial activation and thus increases the risk of vascular amyloid and brain microhemorrhage [156] , [157] , [158] . In contrast, deglycosylated anti-Aβ antibodies greatly reduce such incidents while still retaining the properties of cognition-enhancing and amyloid sequestration [159] , [160] , [161] , [162] . In another study, deglycosylation has been shown to convert pathogenic neuromyelitis optica (NMO)-IgG autoantibodies into therapeutic blocking antibodies [163] .…”
Section: Therapeutic Exploitation Of Antibody Glycoformsmentioning
confidence: 99%